APLIKASI MODEL “JAGAT KERTIH JAVYAKARANA” DALAM MENINGKATKAN PARTISIPASI PENGELOLAAN SAMPAH RUMAH TANGGA DI KECAMATAN MENGWI - Posmaningsih, Dewa Ayu Agustini; Hadi, M.Choirul Hadi; Sri Dhyanaputri, I Gusti Ayu (Jurnal Skala Husada : The Journal of Health, 2023)
Traditional institutions in Bali play a big role in the development process. Traditional institutions can play the role of Agent of modernization in addition to maintaining discipline and order in community development. Jagat Kertih Javyakarana is a model of community empowerment which is an implementation of the results of research that community participation in waste management is influenced by variables of knowledge, attitudes, economic benefits, facilities and local institutions. Institutions There will carry out activities to increase knowledge, change attitudes, increase economic benefits and provide waste management facilities. The research is an experimental research design with Pre Test Post Test Control Group Design. The study was conducted in March - December 2019. The research was conducted in Mengwi District. The study sample was 100 people. The research respondents are housewives. Data analysis was performed with a different free sample test with the help of computer software. The results of the study are known with the value of t -1.18 and sig (2 tailed) 0.24 α (0.05) meaning that there is no significant difference in the average count of community participation in the control group and the treatment group before applying the Jagat Kertih Javyakarana model is the same. After treating the values of t (10.19) and sig (2 tailed) 0.00 α (0.05) it means that there are significant differences in the average count of community participation in the control group and the treatment group after the application of Jagat Kertih Javyakarana model. This model can be used in health promotion activities in Bali Province related to household waste management problems.